Қайырымдылық қызметтегі конфессиялық факторды талдау - Ismail, N. O. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2021)
Traditions of religious charity are leading from the beginning, perhaps, from the very times when blissful charm appears as it is. In the sacred texts of all religions, matters of mercy have a special place. On the one hand, help those who need it, there is a prescription or direct demand in different religions and religious communities. The main purpose of this article is to make a comparative analysis of the ideas of charity in such religious as Islam, Christianity (catolics, righteous, including the antiquity) of history. General features and differences between views on charity in these confessions are deduced. It was revealed that in Judaism there is a measure of permanent disbursements in favor of the poor and the uncommon – tzdaka, tenth part of the income. A similar norm is found both among Muslims and Christian communities. In any religious culture, be it to Islam, Orthodox or Catholic Christianity, Protes- tantism, Judaism speaks of the importance of charity and assistance to people in need. It is also presumed in what way the charity should be produced. From all of the above, it is possible to conclude that religion has imposed a serious imprint on the development of charity in different regions of the world. Key words: charity, religious charity, mercy, philanthropy, Islam, sadaqah.